EVALUASI KELAYAKAN STRUKTURAL DAN KEPADATAN LAPISAN AC-BC MENGGUNAKAN METODE CORE DRILL - Gusrinaldi, Ilham; Imani, Rafki; Alfa, Akbar (Construction and Material Journal, 2025)
The Asphalt Concrete-Binder Course (AC-BC) layer has an important structural function as a binder between the base layer and the wearing layer. This study aims to evaluate the feasibility of the AC-BC layer in terms of thickness and density using the core drill method on the Padang-Pekanbaru Toll Road Section 2 project. Tests were conducted on field and laboratory samples, then the results were compared with the 2018 General Bina Marga Specifications Revision 2. The average thickness of most samples met the minimum standard of 6.0 cm, but there were several points with a thickness <6.0 cm that required evaluation. Field density values ​​ranged from 2.29-2.34 gr/cm³, and degree density between 97.19–99.47%. Most test points met the standard ≥98%, but there were points with values ​​below the standard indicating potential imperfections in the compaction process. Analysis showed that differences in density values ​​were influenced by the mixture temperature during spreading, the delay time between production and spreading, and variations in field implementation. These findings demonstrate the importance of temperature and time control to ensure the quality of AC-BC layer construction. The results of this study can serve as a technical reference for evaluating and improving fieldwork quality in pavement construction projects.